2018
DOI: 10.1002/adom.201801017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Tunable Bilayer Composite Grating for Unique Light Manipulation and Information Storage

Abstract: Composite gratings play important roles in modern information technology. However, such gratings are generally based on the same structural pattern with limited types, and their structural parameters are difficult to tune, which greatly limit their application. A mechanically tunable composite grating in bilayer film, which orthogonally couples a sinusoidal phase grating and a rectangular phase grating, is developed here. The structural parameters of the grating can be well tuned by mechanically stretching or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In the literature, the Poisson's ratio of the oxide layer is generally set to about 0.25. [1,15,29] So, in all calculations of SiO 1.8 /PDMS bilayers, we also set the value of μ m to 0.25.…”
Section: Young's Modulus Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the Poisson's ratio of the oxide layer is generally set to about 0.25. [1,15,29] So, in all calculations of SiO 1.8 /PDMS bilayers, we also set the value of μ m to 0.25.…”
Section: Young's Modulus Calculationmentioning
confidence: 99%
“…Oxygen plasma treatment will oxidize the surface of polydimethylsiloxane (PDMS) films. [1][2][3] The presence of surface oxidation is often simply and roughly equivalent to the presence of a stiff layer in many general application scenarios, such as flexible electronics, [4,5] bionics, [6,7] metamaterials, [1,8] and bucklingbehavior studies. [9][10][11] Oxidized surfaces have also been specially studied.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Meanwhile, the evolution of buckling structures is believed to follow multiple routes. [7,13,17] The selection of the generates a stiff silicon oxide layer, [28][29][30] as schematically illustrated in Figure 1a. The atomic ratio of Si to O on the oxidized PDMS film surface is 1.8, as determined by the X-ray photoelectron spectroscopy (XPS) (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the concomitant luminescence or chromic behavior can be readily detected by conventional devices or the naked eyes. [17][18][19][20][21][22] Besides molecular level design, micro/ nanoscale structural designs have also well demonstrated their feasibility in achieving high-performance dynamic optics. [23][24][25][26][27][28][29][30] Zeng et al reported a mechanochromism based on strain-dependent microscale cracks, including a series of reversible adaptive optics capable of changing transparency, luminescent intensity, fluorescent color, and revealing/concealing patterns by means of stretching/ releasing.…”
Section: Introductionmentioning
confidence: 99%